Bibliotheca symbolica ecclesiæ universalis: The creeds of Christendom, with a history and critical notes - Schaff, Philip (Harper & brothers, 1919)
I. The history of creeds. 6th ed., rev. and enl.--II. The Greek and latin creeds, with translations.--III. The evangelical Protestant creeds, with translations. 4th ed., rev. and enl.